2018
DOI: 10.1093/cercor/bhy215
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Makes a Group be More Creative

Abstract: This study investigated how cooperative and competitive interaction modes affect the group creative performance. The participants were recruited as dyads to solve 2 problems either demanding divergent thinking (alternative uses task, AUT) or not (object characteristic task, OCT). The dyads solved 1 of the 2 problems in the cooperative mode and the other in the competitive mode. Functional near-infrared spectroscopy (fNIRS)-based hyperscanning was used to record their neural activities in the prefrontal and rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 115 publications
2
59
0
1
Order By: Relevance
“…Seven J o u r n a l P r e -p r o o f studies employed these experimental paradigms (Table 3), and all but one used fNIRS. IBS was predominantly identified either in the frontal (Fishburn et al, 2018;Lu et al, 2019a;Lu and Hao, 2019;Lu et al, 2020) or both the frontal and the temporal-parietal regions (Antonenko et al, 2019;Lu et al, 2019b;Mayseless et al, 2019;Xue et al, 2018). Fishburn et al (2018) reported IBS in the PFC for triads cooperatively solving creative…”
Section: Cooperation Problem-solving and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Seven J o u r n a l P r e -p r o o f studies employed these experimental paradigms (Table 3), and all but one used fNIRS. IBS was predominantly identified either in the frontal (Fishburn et al, 2018;Lu et al, 2019a;Lu and Hao, 2019;Lu et al, 2020) or both the frontal and the temporal-parietal regions (Antonenko et al, 2019;Lu et al, 2019b;Mayseless et al, 2019;Xue et al, 2018). Fishburn et al (2018) reported IBS in the PFC for triads cooperatively solving creative…”
Section: Cooperation Problem-solving and Creativitymentioning
confidence: 99%
“…The effects of cooperation, problem-solving, and creativity in relation to IBS have been popular topics of study in ecological settings (Antonenko et al, 2019;Fishburn et al, 2018;Lu and Hao, 2019;Lu et al, 2019aLu et al, , 2019bLu et al, 2020;Mayseless et al, 2019). Seven J o u r n a l P r e -p r o o f studies employed these experimental paradigms (Table 3), and all but one used fNIRS.…”
Section: Cooperation Problem-solving and Creativitymentioning
confidence: 99%
“…Recent social neuroscience studies have reported interactions between the brains of a group of members measured as inter-brain synchronization (e.g., phase synchrony). This synchrony can be enhanced during intense socialization, body or speech coordination, music production, dancers, student-teacher interactions in classrooms, touch-mediated pain reduction, creativity in cooperative tasks, and even in socially interacting bats (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Hence, it can be a metric for more effective group interactions.…”
Section: Team Flow As a Bonafide Inter-brain Statementioning
confidence: 99%
“…The normalized power was calculated through subtracting the individual's mean PSD from the PSD at each condition. The normalized power was averaged within the following frequency bands: delta (1 -3 Hz), theta (4 -7 Hz), alpha (8)(9)(10)(11)(12), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), gamma (31 -120 Hz), and lower gamma (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The normalized power for the 128 channel data and the permutation statistics with Bonferroni multiple comparison correction was projected to topographical maps using EEGLAB toolbox.…”
Section: Power Spectrum Analysismentioning
confidence: 99%
“…The participants' trait creativity was measured procedure using the two classical tests of the AUT and the RAT. The AUT and RAT have different focuses, with the former focused on divergent thinking and the latter on convergent thinking [42,52,53]. As several trait factors (i.e., openness, emotion intelligence) have been reported to moderate the state-level mood-creativity relationship and trait creativity can be regarded as an integrated concept possibly covering all creativity-related trait factors, we expected to see a moderating role of trait creativity on the state-level mood-creativity relationship.…”
Section: Introductionmentioning
confidence: 99%